FATTY ACID COMPOSITION, CHOLESTEROL, AND FAT-SOLUBLE VITAMINS IN THE MUSCLE, LIVER, AND GONAD OF SHABBOUT (BARBUS GRYPUS, HECKEL 1843) - Harlioglu, A. G. (Akademiai Kiado Zrt, 2014)
The moisture, protein, fat, and ash contents of Barbus grypus muscle were 76.14, 18.85, 2.95, and 0.83%, respectively. The fatty acid composition of B. grypus showed that the amounts of saturated fatty acids (SFA) were significantly (P<0.05) higher (34.88%) in the liver compared to the muscle (30.18%). Of the SFA, the amount of palmitic acid was significantly (P<0.05) higher in the liver than that in the muscle and gonad. With regard to the monounsaturated fatty acids (MUFA), oleic acid content in the muscle (23.46%) of B. grypus was significantly (P<0.05) higher than in the liver (18.01%). The amounts of docosahexaenoic acid (C22: 6 n-3, DHA), eicosatetraenoic acid (C20: 4 n-3), and eicosapentaenoic acid (C20: 5 n-3, EPA) were predominantly found in the muscle, liver, and gonad. The amount of cholesterol in the liver and gonad was significantly higher than in the muscle. On the other hand, significantly higher (P<0.05) retinol, D-3, delta-tocopherol, and K-1 vitamin values were found in the liver than in the muscle and gonad of this species.
Keywords: Barbus grypus; fatty acids; proximate composition; cholesterol; muscle; liver; gonad